Fabrication of Stable Superhydrophobic Coatings with Bicomponent Polyurethane/Polytetrafluoroethylene Composites - Liu, Hu; Shang, Qianqian; Xiao, Guomin; Lv, Jianhua (Asian Journal of Chemistry, 2011)
A superhydrophobic coating was fabricated with bicomponent polyurethane/ polytetrafluoroethylene (BPUR/PTFE) composites. Bicomponent polyurethane was obtained by cross-linking reaction between polyisocyanate and hydroxylic fluoroacrylate resin, which was synthesized via free radical polymerization. Superhydrophobic surface with water contact angle of 158º and sliding angle of 2º was obtained from bicomponent polyurethane and polytetrafluoroethylene at their weight ratio of 2/3 by a simple procedure. An irregular rough structure with dispersed grooves and protuberances observed by scanning electron microscope was considered to be responsible for the surface superhydrophobicity. The coating adhered strongly to the substrate and was stable to corrosive medium. The technique is facile, economical and can be expected for large-scale application in anticorrosion and related areas.